2021
DOI: 10.2147/cmar.s330232
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytokines Released During Pyroptosis in Non-Small Cell Lung Cancer

Abstract: Purpose Pyroptosis is a recently discovered highly inflammatory form of programmed cell death, during which the N-terminus of the cleaved Gasdermin protein family forms pores in the cell membrane, leading to cell disintegration and the release of certain intracellular factors, including caspase3, gasdermin E (GSDME), and high mobility group proteins (HMGB1), which trigger a series of secondary inflammatory reactions. Specifically, caspase3 can lyse GSDME and induce pyrolysis, while HMGB1 is releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Lung cancer is the most ubiquitous and lethal malignancy worldwide [ 103 ]. Recent mechanistic work revealed that GSDME knockdown can trigger the transition from apoptosis-to-pyroptosis in lung cancer lines, confirming the hypothesis that GSDME expression determines the type of cell death in caspase-3-activated tumor cells [ 104 ]. In A549 cells, dasatinib can trigger pyroptosis and elevate GSDME levels in A549 cells without the involvement of p53 [ 105 ].…”
Section: Role Of Gsdme-mediated Pyroptosis In Cancer Therapymentioning
confidence: 63%
“…Lung cancer is the most ubiquitous and lethal malignancy worldwide [ 103 ]. Recent mechanistic work revealed that GSDME knockdown can trigger the transition from apoptosis-to-pyroptosis in lung cancer lines, confirming the hypothesis that GSDME expression determines the type of cell death in caspase-3-activated tumor cells [ 104 ]. In A549 cells, dasatinib can trigger pyroptosis and elevate GSDME levels in A549 cells without the involvement of p53 [ 105 ].…”
Section: Role Of Gsdme-mediated Pyroptosis In Cancer Therapymentioning
confidence: 63%
“…(B) Immunohistochemistry of the CHMP4A, HMGB1 and PLK1 was determined in HCC tissues and normal tissues from the HPA database. (41). In breast cancer, HMGB1 translocation was demonstrated to be associated with pyroptosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HMGB1 functioned as the executor of pyroptotic cell death to participate in the regulation of tumor immune microenvironment via the inhibition of mutant BRAF and MEK ( 40 ). High expression of HMGB1 was found in lung cancer tissues, and its release upon pyroptotic cell destruction could be used as a prognostic marker of survival ( 41 ). In breast cancer, HMGB1 translocation was demonstrated to be associated with pyroptosis ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The above results indicated that GSDMD can be regard as an independent prognostic biomarker in LUAD patients. Meanwhile, the expression level of GSDME in lung cancer tissue is significantly higher than that in adjacent tissue, patients with lung cancer having a high GSDME expression have less lymph node metastasis and longer postoperative survival, although the decrease in GSDME level was not significantly correlated with tumor size, clinical stage, age, or tumor recurrence rate (55,110). In addition, the expression level of GSDME was positively correlated with that of caspase-3, and hence caspase-3 is also an important prognostic biomarker in lung cancer patients (55).…”
Section: The Prognostic Role Of Pyroptosisrelated Biomarkers In Nsclc...mentioning
confidence: 99%